Design of a Network of Reverse Logistics: Case Study Usochicamocha – Boyacá (2017)
This paper presents the final results of an advance investigation in the Usochicamocha irrigation district of the Department of Boyacá - Colombia, which faces a problem because of the non - return and collection of al the empty packaging and packaging of pesticides that generate the farmers. Due to the above, the research proposes a configuration and operation of the reverse logistics network (LI) for the collection, collection and final disposal of pesticide residues in that area, for which a linear programming model was developed mixed in order to define both the quantities to be collected and transported to final disposal and to evaluate the possibility of opening new collection centers. The results of the mathematical model show that, on average, 5 kg of waste are collected on each farm and 1106.58 kg are sent to safe disposal and 1292.31 kg to be recycled.